Understanding Biofilm Formation in Ecotoxicological Assays With Natural and Anthropogenic Particulates - Gorokhova, Elena; Motiei, Asa; El-Shehawy, Rehab (Frontiers in Microbiology, 2021)
Fossil-made polymers harbor unique bacterial assemblages, and concerns have been raised that ingested microplastic may affect the consumer gut microbiota and spread pathogens in animal populations. We hypothesized that in ecotoxicity assay with a mixture of polystyrene (PS) and clay (1) microbiome of the test animals inoculates the system with bacteria; (2) relative contribution of PS and the total amount of suspended solids select for specific bacterial communities, and (3) particle aggregation is affected by biofilm community composition, with concomitant effects on the animal survival. Mixtures of PS and clay at different concentrations of suspended solids (SS; 10, 100, and 1000 mg/L) with a varying microplastic contribution (%PS; 0 to 80%) were incubated with Daphnia magna, whose microbiome served as an inoculum for the biofilms during the exposure. After 4-days of exposure, we examined the biofilm communities by 16S rRNA gene sequencing, particle size distribution, and daphnid survival. The biofilm communities were significantly different from the Daphnia microbiota used to inoculate the system, with an overrepresentation of predatory, rare, and potentially pathogenic taxa in the biofilms. The biofilm diversity was stimulated by %PS and decreased by predatory bacteria. Particle aggregate size and the biofilm composition were the primary drivers of daphnid mortality, with small particles and predatory bacteria associated with a higher death rate. Thus, in effect studies with solid waste materials, ecological interactions in the biofilm can affect particle aggregation and support potentially harmful microorganisms with concomitant effects on the test animals.